Study of the fracture surface morphology of impact and tensile tested cast and forged (C&F) Grade 91 steel at room temperature for different heat treatment regimes. (January 2017) - Pandey, Chandan; Saini, Nitin; Mahapatra, Manas Mohan; Kumar, Pradeep
Abstract: Cr-Mo creep strength enhanced ferritic (CSEF) steels are mainly used in nuclear reactors and ultra-supercritical (USC) power plants for superheater tubes and header. The present research deals with the analysis of fracture surface of the tensile and impact tested specimen of cast and forged (C&F) modified 9Cr-1Mo (P91) steels, which are subjected to different heat treatment regimes. The heat treatment temperatures were 350 °C, 650 °C, 760 °C and 1000 °C, respectively. The heat treatment was carried out a particular temperature for 2 h duration. The fracture surface of tensile and impact tested specimen were also studied for a varying time duration from 2 h to 8 h for a fixed tempering temperature of 760 °C. The heat treatment effect on tensile properties, toughness, Vickers hardness and particle size was also studied. Heat treatment has a noticeable effect on mechanical properties of C&F Grade 91 (X10CrMoVNNB9-1) steel. Fracture morphology is strongly affected by the microstructure and presence of secondary phase particles. The fracture surface was analyzed by using the field-emission scanning electron microscope (FE-SEM). The fractured tensile sample mainly indicates the presence of transgranular ductile dimples and transgranular cleavage facets for heat treatment temperatures of 350 °C, 1000 °C and 1040 °C. The percentage of cleavage facets on the tensile fracture surface was found to decrease for sample heat treated at 760 °C. Less amount of ductile dimples was noticed on the fracture surface for the samples heat treated at 650 °C and 760 °C (furnace-cooled). The so-called 'splitting' fracture was noticed for the sample heated at 760 °C. The 'splitting' fracture becomes more pronounced with the increase in tempering duration from 2 h to 8 h. The sample heat treated for 1000 °C, mainly indicates the cleavage facets on the fracture surface. The fracture mode of impact tested specimen is more complex and shows both ductile dimple tearing and quasi-cleavage facets for heat treatment temperature of 650 °C, 760 °C and as-received condition. The impact failure zone of sample heat treated at 350 °C and 1000 °C indicates the presence of so-called 'river pattern' on the fracture surface. Highlights: Effect of heat treatment regimes on mechanical properties of cast-forged Grade 91 steel Effect of varying tempering time on mechanical properties of Grade 91 steel Effect of heat treatment regimes on fracture morphology of tensile tested (room temperature) cast-forged Grade 91 steel Effect of heat treatment regimes on fracture morphology of impact tested (room temperature) cast-forged Grade 91 steel Effect of varying tempering time on fracture mechanism of impact and tensile tested Grade 91 steel